Knowledge and practices on physical activity interventions among breast cancer patients in Nuclear, Radiotherapy and Oncology Department (NROD), Hospital Universiti Sains Malaysia - Ismail, Nor Izati (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Background: Knowledge regarding the important of practices on physical activity is very important among breast cancer patients for their awareness to improve quality of life. Physical activity and exercise among cancer patients has been linked to reduce cancer related fatigue and nausea symptoms as well improve the immune system function of the patients. There are few references on this subject in the literature. The aim of this study was to investigate the knowledge and practices on physical activity among cancer patients in NROD, Hospital USM.